Pemanfaatan Instagram Dalam Membangun Citra Positif Bank Jogja - Abed Nego Putra Pratama (STIKes Ibnu Sina Ajibarang, 2024)
The development of technology has resulted in more and more social media platforms appearing that can be used with various functions. Instagram is a social media application that is very popular with Indonesian people. Instagram is the application with the most users in Indonesia which is not only used as a means of entertainment, but Instagram can also be used to build branding for a company, such as Bank Jogja. The Instagram application is used by Bank Jogja to build a positive image with the name Instagram @bprbankjogja. This research aims to determine the use of Instagram in building a positive image of Bank Jogja. The method used in this research is descriptive qualitative with a case study approach with PII analysis. The analysis is divided into three stages, namely preparation, implementation and impact. The subject in this research is Bank Jogja's Instagram @bprbankjogja. The data collection techniques used in this research were observation and interviews. In achieving success in maintaining the positive image of Bank Jogja, currently using Instagram @bprbankjogja, the impact is quite large in disseminating information so that it can cover all groups. Judging from @bprbankjogja's Instagram content about products that are one of the attractions of society by offering this convenience, this has a big impact on society.